2013
DOI: 10.1080/00224499.2013.816260
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Sexuality in Indonesian Adults with a Disorder of Sex Development (DSD)

Abstract: In Indonesia, disorders of sex development (DSDs) are not well recognized and medical care for affected individuals is scarce. Consequently, many patients live with ambiguous genitalia and appearance. We compared reported outcomes on body image, sexual functioning, and sexual orientation of 39 adults with DSDs (aged 18 to 41) and 39 healthy controls matched for gender, age, and residential setting (urban, suburban, rural). Differences in gender and treatment status (treated or untreated) were also explored. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
4
29
0
3
Order By: Relevance
“…For some of the patients it is difficult to cope, and difficulties in coping may lead to the development of emotional problems such as depression and anxiety. The findings in this study are in line with previous findings in a study on sexuality; women with DSD reported sexual distress, fear of rejection, and avoidance to enter romantic relationships [18]. Our findings underline that it is important that patients with DSD will be referred immediately after identification of their condition to a specialized, multidisciplinary teams.…”
Section: Discussionsupporting
confidence: 92%
“…For some of the patients it is difficult to cope, and difficulties in coping may lead to the development of emotional problems such as depression and anxiety. The findings in this study are in line with previous findings in a study on sexuality; women with DSD reported sexual distress, fear of rejection, and avoidance to enter romantic relationships [18]. Our findings underline that it is important that patients with DSD will be referred immediately after identification of their condition to a specialized, multidisciplinary teams.…”
Section: Discussionsupporting
confidence: 92%
“…26,44 Supporting evidence for early surgery suggests that high rates of stress in mothers, social stigmatization, and isolation of the child and adverse psychosexual development could be avoided by early surgical treatment. 58,60,61 Women, who had undergone surgery, when asked about the optimal timing of surgery, preferred scheduling the feminizing procedure in early childhood. [62][63][64] On the other hand, altered physical sex development does not usually represent a surgical emergency for newborns.…”
Section: Current and Emerging Therapies -Ethical Challengesmentioning
confidence: 99%
“…14 Adult untreated patients either they already changed their gender or still undecided gender were suffered from stigmatization and gender dysphoria and need thorough psychological assessment. [15][16][17] Culture is an important part of the context in which decisions are made on sex assignment. Attitudes concerning gender and sexuality, including the acceptance of intersexuality, may differ between various cultures.…”
Section: Discussionmentioning
confidence: 99%